Main Clinical Features of COVID-19 and Potential Prognostic and Therapeutic Value of the Microbiota in SARS-CoV-2 Infections - He, Yu; Wang, Jianhui; Li, Fang; Shi, Yuan (Frontiers in Microbiology, 2020)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome (SARS) coronavirus 2 (SARS-CoV-2), has become a pandemic, infecting more than 4,000,000 people worldwide. This review describes the main clinical features of COVID-19 and potential role of microbiota in COVID-19. SARS-CoV and SARS-CoV-2 have 79.5% nucleotide sequence identity and use angiotensin-converting enzyme 2 (ACE2) receptors to enter host cells. The distribution of ACE2 may determine how SARS-CoV-2 infects the respiratory and digestive tract. SARS and COVID-19 share similar clinical features, although the estimated fatality rate of COVID-19 is much lower. The communication between the microbiota and SARS-CoV-2 and the role of this association in diagnosis and treatment are unclear. Changes in the lung microbiota were identified in COVID-19 patients, and the enrichment of the lung microbiota with bacteria found in the intestinal tract is correlated with the onset of acute respiratory distress syndrome and long-term outcomes. ACE2 regulates the gut microbiota by indirectly controlling the secretion of antimicrobial peptides. Moreover, the gut microbiota enhances antiviral immunity by increasing the number and function of immune cells, decreasing immunopathology, and stimulating interferon production. In turn, respiratory viruses are known to influence microbial composition in the lung and intestine. Therefore, the analysis of changes in the microbiota during SARS-CoV-2 infection may help predict patient outcomes and allow the development of microbiota-based therapies.